Motion Correction using Coil Arrays (MOCCA) for Free-Breathing Cardiac Cine MRI - Hu, Peng (Magn Reson Med, 2011)
In this study, we present a motion compensation technique based on coil arrays (MOCCA) and evaluate its application in free-breathing respiratory self-gated cine MRI. MOCCA takes advantages of the fact that motion-induced changes in k-space signal are modulated by individual coil sensitivity profiles. In the proposed implementation of MOCCA self-gating for free-breathing cine MRI, the k-space center line is acquired at the beginning of each k-space segment for each cardiac cycle with 4 repetitions. For each k-space segment, the k-space center line acquired immediately before was used to select one of the 4 acquired repetitions to be included in the final self-gated cine image by calculating the cross-correlation between the k-space center line with a reference line. The proposed method was tested on a cohort of healthy adult subjects for subjective image quality and objective blood-myocardium border sharpness. The method was also tested on a cohort of patients to compare the left and right ventricular volumes and ejection fraction measurements with that of standard breath-hold cine MRI. Our data indicate that the proposed MOCCA method provides significantly improved image quality and sharpness compared to free-breathing cine without respiratory self-gating, and provides similar volume measurements compared with breath-hold cine MRI.